Paradoxical Association of Postoperative Plasma Sphingosine-1-Phosphate with Breast Cancer Aggressiveness and Chemotherapy. (24th September 2017) - Ramanathan, Rajesh; Raza, Ali; Sturgill, Jamie; Lyon, Debra; Young, Jessica; Hait, Nitai C.; Takabe, Kazuaki
Abstract : Sphingosine-1-phosphate (S1P) is a bioactive lipid mediator that has been shown to serve an important regulatory function in breast cancer progression. This study analyzes plasma S1P levels in breast cancer patients undergoing adjuvant therapy as compared to healthy control volunteers. 452 plasma S1P samples among 158 breast cancer patients, along with 20 healthy control volunteers, were analyzed. Mean S1P levels did not significantly differ between cancer patients and controls. Smoking was associated with higher S1P levels in cancer patients. Baseline S1P levels had weak inverse correlation with levels of the inflammatory mediator interleukin- (IL-) 17 and CCL-2 and positive correlation with tumor necrosis factor alpha (TNF- α ). Midpoint S1P levels during adjuvant therapy were lower than baseline, with near return to baseline after completion, indicating a relationship between chemotherapy and circulating S1P. While stage of disease did not correlate with plasma S1P levels, they were lower among patients with Her2-enriched and triple-negative breast cancer as compared to luminal-type breast cancer. Plasma S1P levels are paradoxically suppressed in aggressive breast cancer and during adjuvant chemotherapy, which raises the possibility that postoperative plasma S1P levels do not reflect S1P secretion from resected breast cancer.